Dual Role of Indoles Derived From Intestinal Microbiota on Human Health - Ye, Xuewei; Li, Haiyi; Anjum, Komal; Zhong, Xinye; Miao, Shuping; Zheng, Guowan; Liu, Wei; Li, Lanjuan (Frontiers in Immunology, 2022)
Indole and its derivatives in the human body are Tryptophan metabolites by intestinal bacteria. Indole and its derivatives have anti-inflammatory and signal transduction effects and can coordinate the competition among bacteria, which maintain the balance of human intestinal flora, and further affect the immune system’s function. Indoles can regulate the intestinal tract through various receptors and mechanisms and significantly impact human health. While Indoles play an essential role in intestinal microecology, the disadvantages should not be ignored. For example, indoxyl sulfate, a metabolite, has nephrotoxicity and cardiovascular toxicity at high concentrations. Therefore, this paper reviews the correlation of indoles with intestinal microecology to provide a scientific basis for related research and make prospects and thoughts for subsequent indoles-related studies.